An Energy-Efficient Collaborative Ground Vibration Measurement Scheme Based on Compressed Sensing and Belief Propagation. (26th June 2014) - Chen, Danqi; Feng, Jilin; Liu, Qiang; Gao, Fangping; Zhang, Yanxia; Wang, Xiaoying
Abstract : Wireless sensor networks (WSNs) can provide crucial and real-time information in many crisis response and management scenarios. For example, in volcano monitoring and the rapid reporting of aftershock information, WSNs detect the ground vibration and transmit the information sufficiently fast to help people survive the disaster. However, the processing and transmission of ground vibration data present a heavy burden for the small nodes of WSNs, and a single sensor node cannot provide accurate results for ground vibration detection. In this paper, we present a promising energy-efficient collaborative ground vibration measurement scheme based on efficient compressed sensing method and belief propagation method using the difference in the signal strength to distribute wireless communication load among sensor nodes, improve the detection probability, and extend the lifetime of this system. The performance was studied via theoretical analysis and simulation experiments, and the results indicated that the system could reconstruct the seismic signal even with a low measurement count; other benefits included decreased energy consumption of the sensor nodes and a considerably increased detection probability because of the proposed belief propagation method.